Development of lightweight engineered wood produced from derived sugarcane bagasse and coir fiber: Evaluation of the bending and thermal properties - Mawardi, Indra; Nurdin, N.; Razak, Hanif; Amalia, Ismi; Sariyusda, Sariyusda; Aljufri, Aljufri; Putra Jaya, Ramadhansyah (Korean Society of Wood Science Technology, 2025)
This study aimed to investigate the bending and thermal properties of lightweight engineered wood produced from sugarcane bagasse and coir fiber as reinforcement, with a mixture of tapioca starch (TPS) and polyvinyl acetate (PVAc) as the matrix. Sugarcane bagasse and coir fibers were prepared with varying weight ratios (30:70, 70:30, and 50:50) and subsequently incorporated into the TPS/PVAc matrix via a molding technique, thus forming the lightweight engineered wood. The bending and thermal properties of the lightweight engineered wood were evaluated. The results demonstrate that increasing the proportion of coir fiber and the percentage of the matrix improves density, bending strength, thermal stability, and resistance. The lowest thermal conductivity, 0.062 W/mK, was observed in sample EW8, which also exhibited a density of 0.26 g/cm3. The engineered wood comprising a 30 wt% sugarcane bagasse and 70 wt% coir fiber mixture, with a TPS/PVAc matrix blend of 70 wt%, exhibited the highest bending modulus of rupture of 2.47 MPa. The study proposes the use of sugarcane bagasse and coir fibers as a potential alternative for building insulation materials in the form of engineered wood.